2015
DOI: 10.1038/ncomms8316
|View full text |Cite
|
Sign up to set email alerts
|

A piRNA-like small RNA interacts with and modulates p-ERM proteins in human somatic cells

Abstract: PIWI-interacting RNAs (piRNAs) are thought to silence transposon and gene expression during development. However, the roles of piRNAs in somatic tissues are largely unknown. Here we report the identification of 555 piRNAs in human lung bronchial epithelial (HBE) and non-small cell lung cancer (NSCLC) cell lines, including 295 that do not exist in databases termed as piRNA-like sncRNAs or piRNA-Ls. Distinctive piRNA/piRNA-L expression patterns are observed between HBE and NSCLC cells. piRNA-like-163 (piR-L-163)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 62 publications
6
114
0
Order By: Relevance
“…Previous works demonstrated that in silico prediction tools [13] allowed to identify new, non-annotated, piRNAs that were then experimentally validated and found to exert important biological activities [14]. Non annotated 21–35 nt long reads from all smallRNA-Seq datasets of CN and HCC samples, generated as described above and first analyzed for known piRNAs, were thus searched for novel piRNAs as described by Mei et al [14].…”
Section: Resultsmentioning
confidence: 99%
“…Previous works demonstrated that in silico prediction tools [13] allowed to identify new, non-annotated, piRNAs that were then experimentally validated and found to exert important biological activities [14]. Non annotated 21–35 nt long reads from all smallRNA-Seq datasets of CN and HCC samples, generated as described above and first analyzed for known piRNAs, were thus searched for novel piRNAs as described by Mei et al [14].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, piRNAs regulated Piwi protein Miwi ubiqutination by enhancing Miwi interaction with an APC/C substrate-binding subunit during late mouse spermatogenesis [17]. Mei et al [55] identified 555 piRNAs in human lung bronchial epithelial (HBE) and non-small cell lung cancer (NSCLC) cell lines. The results indicated that 295 piRNAs were novel piRNA-like sncRNAs or piRNA-Ls.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported, for the first time, that PIWI-interacting RNA likes (piR-Ls), a type of functional small non-coding RNAs (sncRNAs), played critical roles in NSCLC tumorigenesis and differentiation 10 . We have profiled piR-Ls expression in normal human bronchial epithelial (HBE) and NSCLC cells, and we found that LSCC, LADC, and HBE cells could be clearly clustered together on the expression patters of all piR-Ls 10 .…”
Section: Introductionmentioning
confidence: 99%